Rubipodanones A-D, naphthohydroquinone dimers from the roots and rhizomes of Rubia podantha. (January 2018) - Wang, Zhe; Zhao, Si-Meng; Hu, Yan-Yun; Feng, Li; Zhao, Li-Mei; Di, Ying-Tong; Tan, Ning-Hua
Abstract: Four previously undescribed naphthohydroquinone dimers named rubipodanones A-D, together with 19 known quinones containing three known napthohydroquinone dimers named rubioncolin C, methyl 5-hydroxy-dinaphtho[1, 2-2′, 3′]furan-7, 12-dione-6-carboxylate and rubialatin B, were isolated from the roots and rhizomes of Rubia podantha . Their structures and absolute configurations were determined mainly by NMR, X-ray diffraction, and computational methods. Rubipodanones C and D, the glycosides of rubipodanone A and a pair of C-3 epimer, are the first identified dimeric napthohydroquinone glycosides from the Rubia plants. All naphthohydroquinone dimers were evaluated for their cytotoxicities against ten tumor cell lines and effects on the tumor-associated NF-κB signaling pathway, and rubioncolin C showed the best cytotoxicity with IC50 value of 1.53 μM and NF-κB inhibitory activity with IC50 value of 2.97 μM. These results also demonstrated that the key roles of C-3 configuration and sugar group for biological activities of rubipodanone C. Graphical abstract: Four previously undescribed naphthohydroquinone dimers were isolated from the roots and rhizomes of Rubia podantha . These compounds were evaluated for their cytotoxicities against tumor cell lines and effects on the NF-κB signaling pathway. Image 1 Highlights: Four previously undescribed quinones were isolated from Rubia podantha. The absolute configurations were determined by X-ray analysis and ECD data. Rubioncolin C showed significant cytotoxic and NF-κB inhibitory activities.